Developing a Workflow System by Stuart Gibson - Edge, Martin (The Underwater Photographer, 2010)
W ith digital we can immediately review our pictures on the camera LCDand re-shoot where necessary. This creates many shots of the same subject, so it’s essential to have an organised workflow system in order todownload, store, organise, catalogue, and process these photos on ourcomputers. Organising them in this way can be confusing and problematic formany of us. This chapter covers some basic guidelines for managing thethousands of images we can accrue during a dive trip.